Nutrition for cold weather sports
Special attention to adequate fuel and fluids is imperative in cold weather sports. Athletes participating in sports involving multiple training or competition runs (alpine and freestyle skiing, snowboarding, sledding, etc.) need to make a special effort to hydrate. Some of the issues that are unique to these sports include: •Cold temperatures increase the risk of hypothermia and can reduce the desire to eat and drink. •Shivering increases energy expenditure through the use of carbohydrate (glycogen) in the muscle, making the athlete more prone to fatigue. •Location of training and competition can limit access to food and fluid, making the athlete more likely to neglect to fuel and hydrate adequately.